THE FARMLAND VALUATION REVISITED - Xin Li (International Journal of Food and Agricultural Economics, 2016)
Empirical research is scarce concerning the dynamics of farmland markets which inspire the decision to sell farmlands. This paper explores the real option to postpone the sale of land in farmland valuation. In this article, a real options approach is used to analyze farmland prices behavior using historical cash flow and land price information for Illinois. In general, rising farmland values are primarily dependent on agricultural commodity prices and interest rates. Results suggest that uncertainty about future growth and capital gains is a significant component of farmland market value. Furthermore, this research examines several shift factors of the option value of the state’s farmland by taking into account of uncertainty to improve the analysis of farmland market values.